Vision and driving status of older Australians with cataract: an investigation of public hospital waiting lists. (24th July 2016) - Keay, Lisa; Palagyi, Anna; Do, Vu; White, Andrew; Lamoureux, Ecosse; Ivers, Rebecca Q; Pesudovs, Konrad; Stapleton, Fiona; Boufous, Soufiane; McCluskey, Peter
Abstract: Background: Although cataract surgery can restore sight, lengthy waiting times are common in public hospitals in Australia. We investigated the driving status of older people during their surgical waiting period. Methods: Baseline, cross‐sectional data from two prospective cohort studies of patients aged 50 years and older on Australian public hospital cataract surgery waiting lists were analysed. Participants underwent assessment of vision and completed the Driving Habits Questionnaire. The vision status was compared between current drivers and former drivers. Results: Participants (n = 442) were on average 73 ± 8 years of age and approximately half were women (229/442, 52 per cent). Habitual vision was 6/12 +2 on average (0.26 ± 0.21 logMAR). There were 263 (60 per cent) current drivers, 110 (25 per cent) former drivers and 69 participants (16 per cent) who had never driven. Among the current drivers, 82/263 (31 per cent) failed visual acuity requirements for an unconditional drivers' license (6/12 acuity with one or both eyes). The former drivers had worse visual acuity than the current drivers (between group difference 0.12 ± 0.20 logMAR, p < 0.0001) and worse contrast sensitivity (between group difference −0.14 ± 0.22 log units, p < 0.0001). Both high contrast visual acuity and contrast sensitivity were independently associated with still driving. More than half (140/263, 53 per cent) of the drivers believed that their cataract had affected their driving and 23 current drivers (nine per cent) reported a crash in the last 12 months. Conclusion: We report on the level of visual impairment among older drivers waiting for cataract surgery. Approximately one‐third did not meet the required visual acuity standard for driving and hence would require further ophthalmic assessment and a conditional license to continue to drive. Approximately one‐quarter of the surgical candidates were no longer driving and this was associated with greater visual impairment. These findings support a need for timely and appropriately prioritised access to cataract surgical services.